The application of the cognitive component in the translation/interpreting modules at the Department of English, Faculty of Arts, Taiz University - Al-Kenani, Tawffeek Abdou Saeed Mohammed; Ahmad, Abdullah Othman Abdullah (Journal of Educational and Psychological Sciences, 2020)
This study aims to find out to what extent cognitive component is considered in the translation courses at the English Departments at two faculties of Arts at Taiz University, namely Faculty of Arts, main campus and Faculty of Arts, Turba branch. The cognitive component was selected because it plays a vital role in the development of psychophysiological competence of the translator. The sample of the study consisted of all fourth level students at the two faculties for the academic year 2018/2019. The total number of students participating in the study was 203 students. The study mainly used descriptive quantitative methods.The results of the study showed that the level of application of the cognitive component in translation courses is generally lower than the average or hypothetical mean of the scale (165). The average score of the research sample was (80.3645) with a standard deviation of (26.29714), a t-test value of (-45.856) and a level of Significance of (000.) That is, the application of the cognitive component in the current translation courses is very low and almost non-existent. The study recommended that further studies need to be conducted with a view to finding out to what extent cognitive elements in particular and other psycho-physiological aspects in general are considered in the current translation and interpreting programmes. The study has also recommended that certain activities that can enhance the psycho-physiological components of translators/interpreters should be designed and utilized in the translation/interpreting classroom.
Keywords: Cognitive components; memory; perception; attention; emotions; translating; interpreting courses; Taiz University